Resource discoveries and FDI bonanzas - Toews, G; Vezina, P (University of Oxford, 2016)
This paper examines the examines the effect of giant oil and gas discoveries on foreign direct investment in developing economies using a new project-level dataset. We document a large increase in non-extraction FDI in the 2 years following a giant discovery, an event which is unpredictable due to the uncertain nature of exploration. We find that FDI inflows increase by 73% and that this wave is driven by a 37% increase in the number of FDI projects as well as a 22% increases in source countries and a 17% increase in target sectors. We interpret this FDI response as evidence for the news-driven business-cycle hypothesis within a developing country setting and highlight FDI bonanzas as an important development channel for resource rich economies.